Hemichannels: new roles in astroglial function - Orellana, Juan A.; Stehberg, Jimmy (Frontiers in Physiology, 2014)
The role of astrocytes in brain function has evolved over the last decade, from support cells to active participants in the neuronal synapse through the release of “gliotransmitters”. Astrocytes express receptors for most neurotransmitters and respond to them through Ca2+ intracellular oscillations and propagation of intercellular Ca2+ waves. While such waves are able to propagate among neighboring astrocytes through gap junctions, thereby activating several astrocytes simultaneously, they can also trigger the release of gliotransmitters, including glutamate, d-serine, glycine, ATP, adenosine or GABA. There are several mechanisms by which gliotransmitter release occurs, including functional hemichannels. These gliotransmitters can activate neighboring astrocytes and participate in the propagation of intercellular Ca2+ waves, or activate pre- and post-synaptic receptors, including NMDA, AMPA and purinergic receptors. In consequence, hemichannels could play a pivotal role in astrocyte-to-astrocyte communication and astrocyte-to-neuron cross-talk. Recent evidence suggests that astroglial hemichannels are involved in higher brain functions including memory and glucose sensing. The present review will focus on the role of hemichannels in astrocyte-to-astrocyte and astrocyte-to neuron communication and in brain physiology.